Propranolol for infantile hemangioma: An evaluation of its efficacy and safety in Iranian infants - Fatemeh Livani; Pouran Layegh; Behzad Alizadeh; Mohammad Abbasi Tashnizi; Maryam Amin Moghaddam; Ali Taherian (Mashhad University of Medical Sciences, 2016)
Background: Propranolol has been recently indicated to inhibit the rapid growth and involution of infantile hemangioma. In the present study, we investigated the efficacy and safety of propranolol in Iranian infants. Methods: A total of 30 infants with indications for medical intervention, such as large hemangiomas, wounds with or without secondary infection, or active trauma-induced bleeding, were selected. First, a total concentration of 1 mg/kg/day was orally administered to the infants; the dosage further increased (2-3 mg/kg/day) in case the infants experienced no adverse effects. Following weekly (one month after treatment) and monthly (up to six months) follow-ups, hemangioma activity score (HAS) was calculated to evaluate swelling, color of the lesion, and ulcer size. Results: In the present study, infants with the mean age of 5.33±3.50 years received therapy. Improvement was observed in the lesions of all patients, characterized by a significant decline in size, change in color, and reduction in ulcer size (P